Preferences, beliefs, and attitudes about oral fluid and blood-based HIV self-testing among truck drivers in Kenya choosing not to test for HIV - Joanne E. Mantell; Aleya Khalifa; Aleya Khalifa; Stephanie N. Christian; Matthew L. Romo; Eva Mwai; Gavin George; Gavin George; Michael Strauss; Kaymarlin Govender; Elizabeth A. Kelvin (Frontiers Media S.A., 2022)
IntroductionClinical trials in sub-Saharan Africa support that HIV self-testing (HIVST) can increase testing rates in difficult-to-reach populations. However, trials mostly evaluate oral fluid HIVST only. We describe preferences for oral fluid vs. blood-based HIVST to elucidate prior trial results and inform testing programs.MethodsParticipants were recruited from a HIVST randomized controlled trial in Nakuru County, Kenya, which aimed to test the effect of choice between oral HIVST and facility-based testing compared to standard-of-care on HIV testing among truck drivers. We conducted in-depth interviews (IDIs) with purposively sampled trial participants who declined HIV testing at baseline or who were offered access to oral fluid HIVST and chose not to pick up the kit during follow-up. IDIs were conducted with all consenting participants. We first describe IDI participants compared to the other study participants, assessing the statistical significance of differences in characteristics between the two samples and then describe preferences, beliefs, and attitudes about HIVST biospecimen type expressed in the IDIs.ResultsThe final sample consisted of 16 men who refused HIV testing at baseline and 8 men who did not test during follow-up. All IDI participants had tested prior to study participation; mean number of years since last HIV test was 1.55, vs. 0.98 among non-IDI participants (p = 0.093). Of the 14 participants who answered the question about preferred type of HIVST, nine preferred blood-based HIVST, and five, oral HIVST. Preference varied by study arm with four of five participants who answered this question in the Choice arm and five of nine in the SOC arm preferring blood-based HIVST. Six key themes characterized truckers' views about test type: (1) Rapidity of return of test results. (2) Pain and fear associated with finger prick. (3) Ease of use. (4) Trust in test results; (5) fear of infection by contamination; and (6) Concerns about HIVST kit storage and disposal.ConclusionWe found no general pattern in the themes for preference for oral or blood-based HIVST, but if blood-based HIVST had been offered, some participants in the Choice arm might have chosen to self-test. Offering choices for HIVST could increase testing uptake.